Recruitment and retention of rural allied health professionals: a scoping review - McKenzie Peterson; Sarah Nielsen; Devon Olson (Rural and Remote Health, 2024)
Introduction: The purpose of this study was to understand what literature exists to comprehend demographics and predicted trends of rural allied health professionals (AHPs), person factors of rural AHPs, and recruitment and retention of rural AHPs. Methods: A scoping review was completed and reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. Articles were analyzed using three a priori categories of recruitment and retention, person factors, and demographics and trends. Results: Eighty articles met inclusion criteria for the review. Most of the literature came from Australia. Most research studies were qualitative or descriptive. A priori coding of the articles revealed overlap of the a priori codes across articles; however, the majority of articles related to recruitment and retention followed by demographics and trends and person factors. Recruitment and retention articles focused on strategies prior to education, during education, and recruitment and retention, with the highest number of articles focused on retention. Overall, there were no specific best strategies. Demographic data most commonly gathered were age, practice location, profession, sex, gender, previous rural placement and number of years in practice. While person factors were not as commonly written about, psychosocial factors of rural AHPs were most commonly discussed, including desire to care for others, appreciation of feeling needed, connectedness to team and community and enjoyment of the rural lifestyle. Conclusion: The evidence available provides an understanding of what research exists to understand recruitment and retention of AHPs from a recruitment and retention approach, person factor approach, and demographics and trends approach. Based on this scoping review, there is not a clear road map for predicting or maintaining AHPs in a rural workforce. Further research is needed to support increased recruitment and retention of AHPs in rural areas.